Multiple intelligences and humanistic theories on foreign languaje teaching-learning process - Juárez Hernández, Angélica Esperanza; Molina Rosales, Ana Virginia (2024)
How do human beings learn? Are there certain basic principles of learning that apply to all learning situations? Is one theory of learning better than another? The concern of this work is about the study of learning theories, particularly multiple intelligences and humanistic theories. These new trends in learning argue that there is more than one way to learn, more than one way to be “intelligent”. Besides that, they explain that learning is influenced not only by cognitive but also affective and linguistic factors. These processes involve how learners process knowledge through mental and intellectual capacities, and how their feeling and attitudes influence the learning process. Traditional theories of learning all attempt to describe Universal human traits in learning. They explain globally rather than individually the differences across individuals in the way they learn. Today, the most significant discoveries last trends in learning have made, are those describing that even though, we all display inherently human traits of learning, every individual approaches problems or learns information, perceives, filters, stores and recalls such information from a unique perspective. Multiple Intelligences is a theory which deals with cognitive variations in learning. Besides that, the importance of psychology is being recognized by current theories. Humanistic theory, on the other hand emphasizes that the individual in education is first a human being, then a learner. Therefore, affectivity is a strong factor in determining students’ success. For all this, the integration of multimodal learning approaches and affective factors on foreign language teaching optimize students’ learning process.